SCALING THE DIGITAL DIVIDE: HOME COMPUTER TECHNOLOGY AND STUDENT ACHIEVEMENT. - VIGDOR, JACOB L.; LADD, HELEN F.; MARTINEZ, ERIKA (Economic Inquiry, 2014)
Does differential access to computer technology at home compound the educational disparities between rich and poor? Would a program of government provision of computers to early secondary school students reduce these disparities? We use administrative data on North Carolina public school students to corroborate earlier surveys that document broad racial and socioeconomic gaps in home computer access and use. Using within-student variation in home computer access, and across- ZIP code variation in the timing of the introduction of high-speed Internet service, we also demonstrate that the introduction of home computer technology is associated with modest, but statistically significant and persistent negative impacts on student math and reading test scores. Further evidence suggests that providing universal access to home computers and high-speed Internet access would broaden, rather than narrow, math and reading achievement gaps. (JEL I2, J24 )